Optical properties study of a perovskite solar cell film stack by spectroscopic ellipsometry and spectrophotometry - Maria Fernanda Villa-Bracamonte; Jose Raul Montes-Bojorquez; Arturo A. Ayon (Results in Optics, 2024)
Spectroscopic ellipsometry is a reproducible and non-invasive characterization technique that allows the evaluation of multilayered structures. However, it is an indirect technique and requires the use of well-calibrated models to correctly analyze the materials. In this work, we report a multilayer modeling approach to investigate the optical properties of the three layers of interest typically employed on an inverted perovskite solar cells structure, namely, indium-tin-oxide (ITO) as a transparent anode, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) as a hole transport layer, and methylammonium lead iodide (MAPbI3) as the perovskite layer. The parameterized optical constants based on oscillator models were simultaneously fitted to ellipsometry and intensity-transmission data and validated with ultraviolet–visible (UV–Vis) spectroscopy and profilometry. We propose this multilayer modeling approach as a method to be employed throughout the different stages of the fabrication process to study the distinct mechanisms that impact the final performance of a photovoltaic device.